Pengaruh Konsentrasi Ekstrak Etanol Daun Kersen (Muntingia calabura L) Dalam Menghambat Pertumbuhan Bakteri Escherichia coli Metode Difusi - Sugito, Sugito; Suwandi, Edy; Supriyanto, Supriyanto; Dhantriviana, Indah (Jurnal Laboratorium Khatulistiwa, 2022)
A Jamaican Cherry is a plant which is often found on the edge of the road and home garden. The part of the Jamaican cherry plant which is often used is the part of the leaves and fruit. Jamaican cherry leaves have many benefits, one of them is can be used as an antibacterial. This study aims to knowing the effect of ethanol extract of Jamaican cherry leaves on inhibiting the growth of Escherichia coli bacteria diffusion method with a concentration of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% and 90%. This research used a quasi experiment (Quasi experiment design). The population of this study was the Jamaican cherry leaves extracted from JalanAdiSucipto, Kubu Raya Regency. The sample of this research was Jamaican cherry leaf extract with a concentration of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% and 90%. The results it was obtained that the average diameter of the inhibition zone produced by ethanol extract of Jamaican cherry leaves (Muntingiacalabura L) in inhibiting the growth of Escherichia coli bacteria diffusion method was 10% concentration of 13.8 mm, 20% was 15.3 mm, 30% of 16.0 mm, of 40% of 17.0 mm, 50% of 18.2 mm, 60% of 20.5 mm, 70% of 21.2 mm, 80% of 21, 3 mm and 90% at 23.7 mm. effective concentration is it a concentration of 50% with an average inhibition zone of 18,2 mm.The simple linear regression test result obtained a significant value of p of 0,000 <α 0,05 which states that Hais accepted, which means that there is influence ofethanol extract Jamaican cherry inhibiting the growth of Escherichia coli bacteria diffusion method.